Encounters with an unearthly mudstone: Understanding the first mudstone found on Mars. Issue 2 (30th November 2016) - Schieber, Juergen; Bish, David; Coleman, Max; Reed, Mark; Hausrath, Elisabeth M.; Cosgrove, John; Gupta, Sanjeev; Minitti, Michelle E.; Edgett, Kenneth S.; Malin, Mike
Abstract: The Sheepbed mudstone forms the base of the strata examined by the Curiosity rover in Gale Crater on Mars, and is the first bona fide mudstone known on another planet. From images and associated data, this contribution proposes a holistic interpretation of depositional regime, diagenesis and burial history. A lake basin probably received sediment pulses from alluvial fans. Bed cross‐sections show millimetre to centimetre‐scale layering due to distal pulses of fluvial sediment injections (fine‐grained hyperpycnites), fall‐out from river plumes, and some aeolian supply. Diagenetic features include mineralized synaeresis cracks and millimetre‐scale nodules, as well as stratiform cementation. Clay minerals were initially considered due to in situ alteration, but bulk rock chemistry and mineralogy suggests that sediments were derived from variably weathered source rocks that probably contained pre‐existing clay minerals. X‐ray diffraction analyses show contrasting clay mineralogy in closely spaced samples, consistent with at least partial detrital supply of clay minerals. A significant ( ca 30 wt%) amorphous component is consistent with little post‐depositional alteration. Theoretical modelling of diagenetic reactions, as well as kinetic considerations, suggest that the bulk of diagenetic clay mineral formation occurred comparatively late in diagenesis. Diagenetic features (synaeresis cracks and nodules) were previously thought to reflect early diagenetic gas formation, but an alternative scenario of synaeresis crack formation via fabric collapse of flocculated clays appears more likely. The observed diagenetic features, such as solid nodules, hollow nodules, matrix cement and 'raised ridges' (synaeresis cracks) can be explained with progressive alteration of olivine/glass in conjunction with centrifugal and counter diffusion of reactive species. Anhydrite‐filled fractures in the Sheepbed mudstone occurred late in diagenesis when fluid pressures built up to exceed lithostatic pressure. Generating fluid overpressure by burial to facilitate hydraulic fracturing suggests a burial depth of at least 1000 m for the underlying strata that supplied these fluids.